Applications of 3D seismic attribute analysis workflows: a case study from Ness County, Kansas, USA - Meek, Tyler N. (Kansas State University, 2015)
Due to their high resolution and established success rates, 3D seismic surveys have become one of the most important tools in many hydrocarbon exploration programs. Basic interpretation of seismic reflectors alone, however, may result in inaccurate predictions of subsurface geology. Historically, seismic attributes have played a particularly important role in the characterization of the lithological and petrophysical properties of hydrocarbon reservoirs in Kansas channel fill lithofacies. Integration of an analysis based on post-stack seismic attributes may drastically reduce the chances of drilling in unsuitable locations. Previous theses have focused on establishing a suitable 3D seismic attribute analysis workflow for use in the determination of hydrocarbon production potential in areas of Ness County, Kansas, USA (Abbas, 2009; Phillip, 2011). By applying a similar workflow in the analysis of additional 3D seismic and well log data obtained from a nearby area in Ness County, and comparing those results to existing borehole and production data, this study seeks to test the hypothesis that seismic attribute analysis is a crucial component in the delineation of heterogeneous reservoir stratigraphy in Kansas lithologies. Time-structure maps, in addition to time slices of several 3D seismic attributes including amplitude attenuation, acoustic impedance, and event continuity all seem to indicate that five previously drilled dry wells within the study area were outside the boundary of a meandering, Cherokee sandstone body of potential reservoir quality. Additionally, comparisons of the results of this research to previous studies conducted in Ness County have provided an opportunity to assess, and potentially contribute to, paleodepositional interpretations made through the utilization of a similar workflow (Raef et al., in press). The results of this study seem to support a broadly NE-SW trending meandering channel system, which is in agreement with the interpretations of Raef et al., and the findings of Ramaker (2009).
Keywords: Ness County; 3D seismic; Attribute analysis; Case study; Cherokee sand; Geology (0372); Geophysics (0373)